Controlador Fuzzy implementado em FPGA aplicado ao controle de servomotores - Freitas, Jean Cezar Gonçalves de (2019)
In this work we describe the design of a Fuzzy-type intelligent controller in FPGA hardware for servomotors used in robotic manipulators. The controller was first designed in virtual environment, and finally implemented in an FPGA development kit, where it presented an efficient control and according to the project specifications, showing that the marriage between a Fuzzy type controller and FPGA hardware creates a system of flexible control.